Performance of Water-Based Zinc Oxide Nanoparticle Coolant during Abrasive Grinding of Ductile Cast Iron - M. M., Rahman; K., Kadirgama (Hindawi Publishing Corporation, 2014)
This paper presents the performance of ductile cast iron grinding machining using water-based zinc oxide nanoparticles as a coolant. The experimental data was utilized to develop the mathematical model for first- and second-order models. The second order gives worthy performance of the grinding. The results indicate that the optimum parameters for the grinding model are 20 m/min table speed and 42.43 μm depth of cut for single-pass grinding. For multiple-pass grinding, optimization is at a table speed equal to 35.11 m/min and a depth of cut equal to 29.78 μm. The model fit was adequate and acceptable for sustainable grinding using a 0.15% volume concentration of zinc oxide nanocoolant. This paper quantifies the impact of water-based ZnO nanoparticle coolant on the achieved surface quality. It is concluded that the surface quality is the most influenced by the depth of cut(s) and table speed.